Varicella zoster virus related deaths and hospitalizations before the introduction of universal vaccination with the tetraviral vaccine - Alessandra de Martino Mota; Filipe Anibal Carvalho‐Costa (Brazilian Society of Pediatrics, 2016)
Objective: To characterize varicella zoster virus‐related deaths and hospitalizations in Brazil before universal vaccination with the tetravalent (measles, mumps, rubella, and varicella) vaccine, attempting to collect baseline data on varicella morbidity and mortality in order to evaluate the impact of the varicella vaccination program. Methods: Varicella‐associated mortality data were evaluated between 1996 and 2011 and varicella zoster virus‐associated hospitalizations between 1998 and 2013. Data were gathered from the Informatics Department of the Unified Health System, considering the International Classification of Diseases, 10th Revision, code B01. All age groups were assessed. Varicella‐specific mortality rates were calculated and seasonality of varicella‐zoster virus‐associated hospitalizations was described. Results: There were 2334 varicella deaths between 1996 and 2011, 19.3% in infants aged less than 1 year and 36% in children from 1 to 4 years. In infants under 1 year, varicella mortality rates reached 3.2/100,000/year. In children aged 1-4 years, varicella mortality rates reach 1.64/100,000/year. Average annual mortality rates for varicella in Brazil are 0.88/100,000 in infants under 1 year and 0.40/100,000 in children aged 1-4 years. The total number of hospitalizations associated with varicella zoster virus was 62,246 from 2008 to 2013. Varicella‐associated hospitalizations have a seasonal distribution in children, peaking in November. In the elderly, monthly averages of herpes‐zoster‐associated hospitalizations present no significant seasonal variation. Conclusions: Varicella is associated, in the pre‐vaccine period, to significant morbidity and mortality in Brazil. The universal vaccination program is expected to decrease the disease burden from varicella.